Diets and lifestyle in the prevention of diabetes mellitus - Anchundia, Celeste; Aguirre, Dallerly A.; Rivas, Hendy T.; Cedeño, María N.; Andraus, Cesar E. (Revista Gregoriana de Ciencias de la Salud, 2024)
This paper addressed the prevention of type 2 diabetes (T2D), a chronic disease affecting millions of people worldwide, through the adoption of healthy diets and regular physical activity. The aim was to examine how these strategies could reduce the incidence of T2D, highlighting the relationship between overweight, obesity, and insulin resistance. Recent studies were used to demonstrate the effectiveness of caloric restriction and specific dietary patterns, such as the Mediterranean diet, in improving insulin sensitivity and preventing T2D. It was concluded that, although these interventions were effective, the main challenge was maintaining long-term changes, suggesting the need for support programs and public policies that promote healthy lifestyles from an early age.